1996
DOI: 10.1210/endo.137.4.8625904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endothelin-1 on bovine luteal cell function: role in prostaglandin F2alpha-induced antisteroidogenic action.

Abstract: Endothelin-1 (ET-1) a vasoactive peptide, is synthesized and secreted by endothelial cells. In the bovine corpus luteum (CL), endothelial cells constitute a major proportion (53.5%) of total CL cells. This study was designed to examine the effects of ET-1 on bovine luteal cell functions and its involvement in the action of PGF2alpha. To better define the cells implicated in this process, we used CL slices, whole CL-derived cells, and steroidogenic large (LLC) and small (SLC) luteal-like cells. High affinity bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 28 publications
6
65
1
1
Order By: Relevance
“…Namely, pre-exposure of the microenvironment within the bovine mid-CL with PGF2α potentiated the P inhibiting activity of endothelin-1 (ET-1) in the in vitro MDS model, which involves the activation of intracellular Ca 2+ . Consequently, we and others have proposed that a vasoactive peptide such as ET-1 mediates luteolytic actions of PGF2α in the bovine CL [17][18][19]. Recently, we have found that angio- tensin II is a possible additive luteolytic mediator in the bovine CL [20].…”
Section: Discussionmentioning
confidence: 91%
“…Namely, pre-exposure of the microenvironment within the bovine mid-CL with PGF2α potentiated the P inhibiting activity of endothelin-1 (ET-1) in the in vitro MDS model, which involves the activation of intracellular Ca 2+ . Consequently, we and others have proposed that a vasoactive peptide such as ET-1 mediates luteolytic actions of PGF2α in the bovine CL [17][18][19]. Recently, we have found that angio- tensin II is a possible additive luteolytic mediator in the bovine CL [20].…”
Section: Discussionmentioning
confidence: 91%
“…These findings strongly suggest that the invasion of immune cells into the regressing CL is the major reason for the increase of TNF-α concentration in the CL at this period. Recently, we and others have shown that the production and release of endothelin-1, a vasoconstrictive peptide originated from endothelial cells, increased in the CL and ovarian venous plasma ipsilateral to the CL from 2 h after PGF2α injection in the cow, and proposed that endothelin-1 interacts with PGF2α as a local luteolytic factor [21][22][23][24]. It is likely that such vasoconstrictive peptides are responsible for an acute response to luteolytic PGF2α in both 1) direct inhibition of P release and 2) a vasoconstriction of arterioles, and thereby they can start an acute depletion of P release followed by a degeneration of CL tissue in which TNF-α plays a major role.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the administration of a luteolytic dose of PGF 2a rapidly stimulated gene expression for ET-1 in ovine CL collected at mid-cycle (Hinckley & Milvae 2001). It is likely, therefore, that ET-1 released from microvascular endothelial cells in the CL and luteal cells (Levy et al 2001, Schams et al 2003 cooperates with PGF 2a to initiate luteolysis by both directly inhibiting progesterone release (Girsh et al 1996a, Miyamoto et al 1997) via ETA-R (Girsh et al 1996a, Hinckley & Milvae 2001 and probably by vasoconstriction of arterioles that results in an acute drop in progesterone release.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence in the cow suggests that endothelin-1 (ET-1), a vaso-constrictive 21-amino acid peptide, interacts with PGF 2a in the control of functional luteolysis (Girsh et al 1996a,b, Miyamoto et al 1997, Ohtani et al 1998, Meidan et al 1999. This hypothesis has been further supported by in vivo studies in the ewe.…”
Section: Introductionmentioning
confidence: 99%